Kajian Potensi Pembangkit Listrik Tenaga Mikrohidro Di Sungai Wae Bobot Kecamatan Werinama Kabupaten Seram Bagian Timur - Mohamad Achmad Sofyan Kelian (JURNAL SIMETRIK, 2017)
This research study exploiting of potency charge river alternatively resource of energi for the power station ofhydro mini energy ( PLTMH). Case study the evaluated is Wai Bobot River which located in CountrysideFragon Enchain, District Of Field Jar Pate;Upstream, Sub-Province of Werinama Kab. Seram Bagian Timur.Power Station Of Hydro Mini Energy ( PLTMH) expected can be woke up by Local Government Of Sub-Province of Werinama Kab.Seram Bagian Timur to obtain;get energy capacities attached equal to 27 kW to 42house and 0,514 kW to each;every house by exploiting Wai Bobot River. Dimension Building barricade PLTMHspecified from pursuant to River Wai Bobot floods debit equal to Q= 55 m3 / det. Debit plan equal to 0,80 m3 /det obtained from result of direct measurement in field by considering various aspect for example : yieldedenergy, scheme of PLTMH, high fall, turbine operational and also defrayal of work of and civil of elektromekanikallowest.